(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
Ukraine is in a situation of increased danger of emergencies in connection with a continuing international armed conflict on the territory of the country. This creates the need for specialized training of specialists in order to increase the psychological readiness and capacity of communities for effective action in emergencies. The aim is to establish the conceptual grounds for developing disasters community readiness by focused and informed social workers. Creation and approbation of the new high education learning course on the base of theoretical analysis is the proposed way. As the results of analysis are some schemas of dynamics of the communities coping processes during and after disasters and other extremal situations (fire, technological catastrophe, war captivity, historical trauma). It is grounded topics and educational principles of discipline for social rehabilitators professional prepare. The author singles out four approaches for understanding suffering community and collective trauma dynamics (enlightenment, psychoanalytic, socio-constructive and organizational psychological). It is proposed three scales for social psychological analysis of community: urgent, long-term and trans-generative time intervals. Because the content has potential for secondary trauma induction, it is necessary to improve some safe promotional didactic elements: reflexive validity, resourceness, and information ecology principles. Students can choice some additional traumatic situations in local or national communities for joint analysis in the auditorium, which gives empowerment and feelings of co-creation during learning process.